PENGARUH PEMBERIAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN DI PT. X JAKARTA PUSAT - Maria Dwi Yanika Hesti Nugraha; Anggi Nadia Yolanda (Universitas Bunda Mulia, 2011)
Compensation is all income in the form of money, goods directly or indirectly received by an employee in return for services rendered to the company. Job satisfaction is a positive feeling about one's work is the result of an evaluation of its characteristics. The purpose of this study was to determine how important the effect of compensation on job satisfaction of employees at PT. X in Central Jakarta which affects the performance of employees at PT. X, Central Jakarta.This study uses quantitative research methods. Using the questionnaire method. The population in this study are all of the employees of PT. X in Central Jakarta by the number of employees 120 employees. Based on measurements using the formula Yamane then of the whole population of 120 people then the sample in this study as many as 92 people. Based on calculations MAS, showed p-value 0.000 <0.05, significant meaning, while the F count 137.796> F table of 3.96, meaning that significant. This means that compensation affects the job satisfaction of employees. Based on calculations using SPSS 12 for windows (data attached), shows the value of the adjusted coefficient of determination (Adjusted R Square) of 0.601 means that 60.1% of dependent variables of job satisfaction is explained by the independent variable compensation and the remaining 39.9% is explained by other variables outside variables used. When viewed from the calculation then the correlation between job satisfaction variable compensation by showing figure of 0.778. The figure shows a strong correlation and direction. Based on the results of data analysis and discussion that has been presented, it can be concluded that there is a significant relationship between positive towards the provision of compensation to the job satisfaction of employees in PT. X Jakarta. Keyword: Providing Compensation, Work Satisfaction, employeement